Optimality conditions for the calculus of variations with higher-order delta derivatives - Ferreira, R.A.C.
We prove the EulerLagrange delta-differential equations for problems of the calculus of variations on arbitrary time scales with delta-integral functionals depending on higher-order delta derivatives.